2009
DOI: 10.1016/j.bbmt.2009.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Filgrastim-Induced Stem Cell Mobilization after Prior Lenalidomide in Patients with Multiple Myeloma

Abstract: Lenalidomide is an agent that has shown great activity in patients with multiple myeloma. However, studies have suggested that this drug negatively affects subsequent stem cell collection. To investigate whether lenalidomide impairs stem cell mobilization and collection, we reviewed data for patients with multiple myeloma who underwent mobilization with filgrastim. Predictors of mobilization failure were evaluated using logistic regression analysis. In 26 (9%) of 302 myeloma patients, stem cell mobilization fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
146
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 27 publications
(21 reference statements)
10
146
1
6
Order By: Relevance
“…Importantly, the detrimental effect of lenalidomide on HSC mobilization was associated with the extent of exposure, leading to the recommendation that transplant-eligible, lenalidomide-treated patients should undergo HSC collection Preemptive plerixafor in lenalidomide-treated patients LJ Costa et al during the first 6 months of therapy. Multiple subsequent and independent reports confirmed the detrimental effect of lenalidomide on mobilization, with mobilization failure rates up to 25% [8][9][10] along with a dose-dependent effect. 9,10 The use of CY plus growth-factor mobilization is often employed in MM with intent to obtain better CD34 þ yield while still providing anti-MM therapy, although the relevance of the latter has never been demonstrated.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Importantly, the detrimental effect of lenalidomide on HSC mobilization was associated with the extent of exposure, leading to the recommendation that transplant-eligible, lenalidomide-treated patients should undergo HSC collection Preemptive plerixafor in lenalidomide-treated patients LJ Costa et al during the first 6 months of therapy. Multiple subsequent and independent reports confirmed the detrimental effect of lenalidomide on mobilization, with mobilization failure rates up to 25% [8][9][10] along with a dose-dependent effect. 9,10 The use of CY plus growth-factor mobilization is often employed in MM with intent to obtain better CD34 þ yield while still providing anti-MM therapy, although the relevance of the latter has never been demonstrated.…”
Section: Discussionmentioning
confidence: 81%
“…Preliminary experience suggests that the majority of lenalidomide-exposed patients failing filgrastim mobilization will adequately mobilize CD34 þ cells with filgrastim plus plerixafor. 10,19,20 Moreover, there were no mobilization failures among the few reported lenalidomide-treated patients who underwent upfront mobilization with filgrastim plus plerixafor. 20,21 In this study, we examine 89 patients with MM (49 previously exposed to lenalidomide) who proceeded to steady state growth factor-based AHSC mobilization with preemptive ('just in time') use of plerixafor depending on peripheral blood CD34 þ enumeration on the 4th day of mobilization and following a previously validated and published algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the patients were characterized by features that are known to affect standard stem cell mobilization negatively, including advanced age, a diagnosis of NHL, previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, previous autoSCT, or failure of at least one previous attempt at mobilization [7][8][9][10][11][12][13][14][15]. We observed that, despite these unfavorable characteristics, mobilization with plerixafor and G-CSF enabled the required number of stem cells to be collected in 67.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors are known to affect the outcome of stem cell mobilization negatively in the context of traditional mobilization regimens that are based on the administration of G-CSF with or without chemotherapy. These factors include advanced age, a diagnosis of non-Hodgkin's lymphoma (NHL), previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, and the failure of at least one previous attempt at mobilization [7][8][9][10]. In this study, we decided to investigate whether the above-mentioned factors might allow the prediction of a suboptimal outcome for stem cell mobilization with plerixafor and G-CSF.…”
Section: Introductionmentioning
confidence: 99%